Analysis of the Quality of Subdistrict Integrated Administration Services (PATEN) - Asnar, Asnar (International Journal Labs, 2024)
The study analyzed the quality of Subdistrict Integrated Administration Service Delivery (PATEN) at the Samarinda Ilir District Office in Samarinda City, focusing on its supporting and inhibiting factors. The research used a qualitative approach, including purposive and accidental sampling techniques, in-depth interviews, participatory observations, and documentation studies. The results showed good patent implementation quality, as measured by the five dimensions of public service quality analysis: reliability, responsiveness, certainty, empathy, and tangibility. Supporting factors included adequate office service facilities, air conditioning, television, and comfortable seating. However, the inhibiting factor was the lack of informal socialization among the community. The study also highlighted the management of licensing services in the sub-district, following laws and regulations.